Laparoscopic ileopexy for afferent limb syndrome after ileal pouch‐anal anastomosis. Issue 4 (30th June 2017) - Okita, Yoshiki; Araki, Toshimitsu; Hiro, Junichiro; Kondo, Satoru; Fujikawa, Hiroyuki; Yoshiyama, Shigeyuki; Inoue, Mikihiro; Toiyama, Yuji; Kobayashi, Minako; Ohi, Masaki; Inoue, Yasuhiro; Uchida, Keiichi; et al.
Abstract: Afferent limb syndrome (ALS) is caused by an obstruction of the afferent intestinal limb after ileal pouch‐anal anastomosis. Here, we describe the first case of ALS to be successfully treated by a laparoscopic approach. A 27‐year‐old man underwent ileal pouch‐anal anastomosis for ulcerative colitis. He was subsequently diagnosed with ALS and underwent ileopexy with laparotomy at 33 years old. Then, 21 months after the first ileopexy, he underwent laparoscopic ileopexy for ALS recurrence. The operative findings revealed a shortened fixed portion of the afferent limb adhering to the right pelvic retroperitoneum, which was regarded as the cause of the acute angulation. The portion of the afferent limb fixed to the abdominal wall was extended under laparoscopic visualization by suturing above the level of the iliac crest. At the 12‐month follow‐up, the patient remained free of symptoms of obstruction. Laparoscopic ileopexy should be the procedure of choice for patients with ALS.